Utilização da modelagem matemática multiobjetivo na geração de dieta para um restaurante universitário - Delinski, Luciana Maichaki Marçal (2019)
Mathematical modeling can be used in several areas; one of them is the diet generation. A balanced feed contributes to disease prevention, help in well-being and focus, however, for any reason not always the human being is able to have a balanced feed, with the routine change, what usually occurs to university students. This research has as main objective the proposal of a multiobjective mathematical model for the generation of diets. This model has been adapted and tested to generate a diet for University Restaurants, where students usually carry out their main meals. The model considers three main objectives for the diet, the lowest cost, to select foods with higher food preference of the students and to provide the minimum possible amount of cholesterol. These objectives are achieved only if the nutritional requirements of each age range studied are respected. The methodology used is this study was composed by six steps. First the nutritional composition of food data was obtained and the food were selected, as not all foods were practicable to be consumed in main meals and/or in an university restaurant. After this selection the price of food were obtained. It were obtained also the nutritional recommendation for human being, the maximum and minimum energy limits, essential nutrients and vitamins for people from 19 to 24 years old. As one of the objectives of the model is to give food with higher acceptance of students, it were obtained the results of food preference survey realized in UTFPR by the author Spak (2017) and these results were fuzzified. The last step of the methodology was the execution of the multiobjective mathematical model. This model was applied to generate a diet to university restaurant, it was obtained a minimum cost of R$2,96 and selected food with higher acceptance level of students in UTFPR. The conclusion is that the model is able to help in diet generation, it can be adapted to any public, being necessary only the change in used data according to the studied public.